2016
DOI: 10.1007/s10570-016-0924-z
|View full text |Cite
|
Sign up to set email alerts
|

Processing window for extrusion foaming of hydroxypropyl methylcellulose

Abstract: Foamed materials are gaining an increased interest due to their good mechanical properties in relation to their low densities and an increased industrial demand can be expected. A few less attractive issues can however be associated with commodity foamed products. For instance the rawmaterial often originates from non-renewable, fossilbased, sources. Furthermore, degradation in nature is slow, therefor the disposed product is burned or end up in landfills. One possibility to reduce the impact on nature could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The measured T g (being mainly between 170 and 180 °C) are also in accordance with previously reported values for similar cellulose derivatives. Sakellariou et al reported T g -values of HPMC in the range of 169-180 °C depending on experimental conditions and technique used [16] and Karlsson et al measured the T g by DMTA to be in the region 160-170 °C, also for HPMCgrades [17].…”
Section: Dynamic Mechanical Thermal Analysismentioning
confidence: 99%
“…The measured T g (being mainly between 170 and 180 °C) are also in accordance with previously reported values for similar cellulose derivatives. Sakellariou et al reported T g -values of HPMC in the range of 169-180 °C depending on experimental conditions and technique used [16] and Karlsson et al measured the T g by DMTA to be in the region 160-170 °C, also for HPMCgrades [17].…”
Section: Dynamic Mechanical Thermal Analysismentioning
confidence: 99%
“…In addition, methyl cellulose (MC) have been investigated for use in packaging materials [13,14]. It is also known to give foams by using a hot-mould foaming technique [15], as well as by extrusion using water vapour as the blowing agent [16].…”
Section: Introductionmentioning
confidence: 99%